Small and medium enterprises (SMES) competing in the global business environment: A case of Malaysia - Mohd Zulkifli Muhammad; Abdul Kamal Char; Mohd Rushdan bin Yasoa; Zakiah Hassan (Canadian Center of Science and Education, 2010)
Small and Medium Enterprises (SMEs) play a vital role in the country's economic development. The current trend of economic growth and the rapid industrial development has made Malaysia as one of the most open economies in the world. In conjunction with the Ninth Malaysian Plan (2006-2010), the government is devoting and designing the SME development plan to assist the SMEs to meet the new business challenges in the competitive global business environment. The focus of this paper is the discussion of the competitiveness facing SMEs in the global business environment by examining the opportunities and supports from the government. Furthermore, this study also analyses the challenges of Malaysian SMEs in globalize market together with economics turmoil.